ATP allosterically regulates an acyl-CoA oxidase - David H. Perez; Arup Mondal; Weijie Xu; Valentina Baredes; Hannah E. Connell; Alberto Perez; Rebecca A. Butcher (Nature Communications)
Abstract ATP is an important allosteric regulator of many enzymes, but these enzymes typically utilize ATP or other nucleotides as substrates. Acyl-CoA oxidase (ACOX) enzymes are central players in peroxisomal fatty acid metabolism, as well as in secondary metabolism in nematodes and plants. These dimeric enzymes have been shown to bind to ATP at unusual sites that are buried at the dimer interface. Here, we show that ATP stimulates the activity of an ACOX enzyme by increasing the binding affinity of the enzyme for its FAD cofactor. The effect of ATP is highly specific as other nucleotides do not stimulate the activity of the enzyme and mutation of the ATP binding site blocks the effect. We use X-ray crystallography and molecular dynamics simulations of the apo dimeric enzyme to identify an unprecedented mechanism whereby ATP can reach its binding site through a shift in an α-helix bundle. An allosteric network connects the ATP and FAD binding sites, enabling ATP to enhance FAD binding affinity and thus enzymatic activity. In summary, the binding of ACOX enzymes to FAD is allosterically controlled by ATP, potentially providing a link between ATP levels and primary and secondary metabolism.